The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5194/acp-18-227-2018
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation modelling from ground-based and satellite measurements on Reunion Island, southern tropics

Abstract: Abstract. Surface ultraviolet radiation (SUR) is not an increasing concern after the implementation of the Montreal Protocol and the recovery of the ozone layer (Morgenstern et al., 2008). However, large uncertainties remain in the prediction of future changes of SUR (Bais et al., 2015). Several studies pointed out that UV-B impacts the biosphere (Erickson et al., 2015), especially the aquatic system, which plays a central part in the biogeochemical cycle (Hader et al., 2007). It can affect phytoplankton produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
(86 reference statements)
4
14
0
2
Order By: Relevance
“…In most cases, clouds attenuate the UV signal at the surface by about 15 % to 45 % (Calbó et al, 2005). Broken cloud cover can also enhance the surface UV radiation (Lovengreen et al, 2005;Marín et al, 2017). Krzyścin and Puchalski (1998) found a 1.5 % increase in erythemal UV for a 10 % decrease in aerosol optical depth (AOD) and up to a 30 % decreases in UV erythemal can be observed due to biomass burning emissions (Lamy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, clouds attenuate the UV signal at the surface by about 15 % to 45 % (Calbó et al, 2005). Broken cloud cover can also enhance the surface UV radiation (Lovengreen et al, 2005;Marín et al, 2017). Krzyścin and Puchalski (1998) found a 1.5 % increase in erythemal UV for a 10 % decrease in aerosol optical depth (AOD) and up to a 30 % decreases in UV erythemal can be observed due to biomass burning emissions (Lamy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ozone is the dominant attenuator of UVB irradiance and the most important atmospheric factor for its deviations [34]. Aerosol attenuation in UV spectral region is also a non-negligible factor for the irradiance reaching the surface and, in some cases, its effects have been found to be as important as those of ozone [35][36][37][38][39]. Additionally, absorbing aerosols indirectly affect irradiance's variability, by reducing the incident UV irradiance and altering lower atmosphere's photochemistry, thus affecting tropospheric ozone's concentration (up to 50 ppb has been reported) [38].…”
Section: Introductionmentioning
confidence: 99%
“…The instrument inter-comparison was performed only for clear sky conditions. Cloud fraction data were analysed in two ways to determine a clear sky threshold: 1) Lamy et al [18] showed that TUV clear sky outputs could be compared to Bentham clear sky outputs on the same site with differences of less than 5% when TUV was correctly set up. From this result we compared the TUV outputs with the appropriate setting and the Bentham over the reference period in order to determine the cloud fractions (as seen by the camera) corresponding to a difference in UVI of less than 5%.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, during a QASUME campaign [16], a BT/QASUME ratio of −5% to 0% was found [17]. A recent comparison between BT and UVI obtained by modelling showed ± 5% difference [18]. However, since 2009, there have been some gaps in the data due to technical problems and prolonged maintenance delays.…”
Section: Spectroradiometer Bentham Dtmc300mentioning
confidence: 99%